Carbon Nanotubes and Carbon Nanofibers for Enhancing the Mechanical Properties of Nanocomposite Cementitious Materials - Tyson, Bryan M; Abu Al-Rub, Rashid K; Yazdanbakhsh, Ardavan; Grasley, Zachary (Journal of materials in civil engineering, 2011)
Carbon nanotubes (CNTs) and carbon nanofibers (CNFs) are quickly becoming two of the most promising nanomaterials because of their unique mechanical properties. The size and aspect ratio of CNFs and CNTs mean that they can be distributed on a much finer scale than commonly used microreinforcing fibers. As a result, microcracks are interrupted much more quickly during propagation in a nanoreinforced matrix, producing much smaller crack widths at the point of first contact between the moving crack front and the reinforcement. In this study, untreated CNTs and CNFs are added to cement matrix composites in concentrations of 0.1 and 0.2% by weight of cement. The nanofilaments are dispersed by using an ultrasonic mixer and then cast into molds. Each specimen is tested in a custom-made three-point flexural test fixture to record its mechanical properties; namely, the Young’s modulus, flexural strength, ultimate strain capacity, and fracture toughness, at 7, 14, and 28 days. A scanning electron microscope (SEM) is used to discern the difference between crack bridging and fiber pullout. Test results show that the strength, ductility, and fracture toughness can be improved with the addition of low concentrations of either CNTs or CNFs.